Pembelajaran Membatik dengan Zat Pewarna Alam di Studio Batik Kembang Mulyo Jepara - Achmad Luqmanul Khakim; Jati Widagdo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Batik is the art and method of decorating a cloth with a wax covering in which the decorative patterns and patterns are formed using dyes. The two dyes, namely natural dyes and chemical dyes. In its development, natural dyes are increasingly in demand, apart from having beautiful and unique colors, they are also good for the user's skin. For this reason, this article aims to explain natural dyes that can be used as alternative batik dyes. The nature of the research is field research and library research. Research techniques are carried out using various steps, including: Observation techniques. The data that has been obtained is then compiled, classified and analyzed descriptively qualitatively. And to obtain complementary research data using library research techniques. From this study, results were obtained from making batik using various natural dyes. Either those that are often used or new natural dyes that can be used as coloring in making batik. When applying natural dyes, it is recommended to use local materials so that later they can become the characteristic color of Jepara batik and it is recommended to try often, so that the resulting color matches what you want.